Effects of Frontal Transcranial Direct Current Stimulation on Emotional State and Processing in Healthy Humans - Nitsche, Michael A.; Koschack, Janka; Pohlers, Henriette; Hullemann, Sandra; Paulus, Walter; Happe, Svenja (Frontiers in Psychiatry, 2012)
The prefrontal cortex is involved in mood and emotional processing. In patients suffering from depression, the left dorsolateral prefrontal cortex is hypoactive, while activity of the right dorsolateral prefrontal cortex is enhanced. Counterbalancing these pathological excitability alterations by repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) improves mood in these patients. In healthy subjects, however, rTMS of the same areas has no major effect, and the effects of tDCS are mixed. We aimed to evaluate the effects of prefrontal tDCS on mood and mood-related cognitive processing in healthy humans. In a first study, we administered excitability-enhancing anodal, excitability-diminishing cathodal and placebo tDCS to the left dorsolateral prefrontal cortex, combined with antagonistic stimulation of the right frontopolar cortex, and tested acute mood changes by an adjective checklist. Subjective mood was not influenced by tDCS. Emotional face identification, however, which was explored in a second experiment, was subtly improved by a tDCS-driven excitability modulation of the prefrontal cortex, markedly by anodal tDCS of the left dorsolateral prefrontal cortex for positive emotional content. We conclude that tDCS of the prefrontal cortex improves mood processing in healthy subjects, but does not influence subjective mood state.